ANALYSIS OF STUDENT LEARNING READINESS TO FULFIL ACHIEVEMENTS INDEPENDENT CURRICULUM WITH DIFFERENTIATED LEARNING - ZAFA, NUR ‘AFIFAH; ILZAMUDIN, ILZAMUDIN; PERDANA, PURNAMA RIKA (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
This study explores the impact of students' learning readiness on the implementation of differentiated learning to achieve independent curriculum goals in a seventh-grade class at SMPIT Putri Al-Hanif, Cilegon, Indonesia. The theoretical framework emphasizes the dynamic nature of readiness, distinct from innate ability, highlighting the importance of aligning assignments with students' abilities and interests. Employing qualitative descriptive research, the study involves 23 participants, utilizing assessments, interviews, and observations. Results reveal diverse levels of learning readiness influenced by internal and environmental factors. The differentiated learning approach caters to individual needs, emphasizing process, product, content, and learning environment adjustments. Findings underscore the crucial role of teachers in organizing varied learning strategies to enhance students' readiness and overall learning quality within the context of the independent curriculum. This research contributes valuable insights into addressing learning gaps and optimizing educational outcomes in the Era of Revolution 5.0.